CURRICULUM VALIDITY OF NATIONAL EXAMINATION IN ENGLISH SUBJECT 2019 AT SMA NEGERI MATAKALI - Muhammad Arham; Radiah Hamid; Wildhan Burhanuddin (FKIP Unismuh Makassar, 2021)
The purpose of this research is to find out the validity of National Examination’s item 2019 in English Subject in reading skill in SMA Negeri Matakali, KabupatenPolewali Mandar.The research used descriptive quantitative method. The subject of this research is English teacher at SMA NegeriMatakali, Lesson plan of English, Curriculum 2013 and National examination’s document in English subject 2019. The data of the research was taken by using document analysis and interview. The result of this research showed 11 of 50 question’s item in National examination in English subject 2019 are in line with English materials which are taught in SMA Class XII at first semester. It means 22% from the total number of National Examination.